Health plan decision making with new medicare information materials. - McCormack, L A (2001)
OBJECTIVE: To examine the effect of providing new Medicare information materials on consumers' attitudes and behavior about health plan choice. DATA SOURCE: New and experienced Medicare beneficiaries who resided in the Kansas City metropolitan statistical area during winter 1998-99 were surveyed. More than 2,000 computer-assisted telephone interviews were completed across the two beneficiary populations with a mean response rate of 60 percent. STUDY DESIGN: Medicare beneficiaries were randomly assigned to a control group or one of three treatment groups that received varying amounts and types of new Medicare information materials. One treatment group received the Health Care Financing Administrations's pilot Medicare & You 1999 handbook, a second group received the same version of the handbook and a Medicare version of the Consumer Assessment of Health Plans (CAHPS) report, and a third treatment group received the Medicare & You bulletin, an abbreviated version of the handbook. PRINCIPAL FINDINGS: Results of the study suggest that the federal government's new consumer information materials are having some influence on Medicare beneficiaries' attitudes and behaviors about health plan decision making. Experienced beneficiary treatment group members were significantly more confident with their current health plan choice than control group members, but new beneficiaries were significantly less likely to use the new materials to choose or change health plans than control group members. In general the effects on confidence and health plan switching did not vary across the different treatment materials. CONCLUSIONS: The 1999 version of the Medicare & You materials contained a message that it is not necessary to change health plans. This message appears to have decreased the likelihood of using the new materials to choose or change plans, whereas other materials to which beneficiaries are exposed may encourage plan switching. Because providing more information to beneficiaries did not result in commensurate increases in confidence levels or rate of health plan switching, factors other than the amount of information, such as how the information is presented, may be more critical than volume.